Clinical and Immunological Features of the Diffuse Form of Systemic Scleroderma (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In today's article, Scleroderma appears: limited; systematic. Systemic scleroderma is a problem associated with characteristic damage to the skin, blood vessels, musculoskeletal system and internal organs (lungs, heart, digestive system, kidneys).